APPLICATION OF NEW ROAD CONSTRUCTION COMPOSITE MATERIALS IN THE DESIGN OF ROAD OVERFLOW STRUCTURES - Qo‘ysinaliyev, Nuriddin Zafarali o‘g‘li; Abduqaxxorov , Xusniddin Abdusalom oʻg‘li (INTERNATIONAL CONFERENCES, 2023)
The main and additional materials used in the production of geonets are basalt and its application to our roads. Passing the basalt geogrid through the laboratory, determining the levels of traffic loading, studying the characteristics of testing the geogrid’s resistance to stretching, and its application and use areas.